Deacetylation of HSC70-4 Promotes Bombyx mori Nucleopolyhedrovirus Proliferation via Proteasome-Mediated Nuclear Import - Mao, Fuxiang; Chen, Xi; Ngowo, Jonas; Zhu, Yajie; Lei, Jihai; Gao, Xu; Miao, Meng; Quan, Yanping; Yu, Wei (Frontiers in Physiology, 2021)
Silkworm (Bombyx mori) is a model organism with great agricultural economic value that plays a crucial role in biological studies. B. mori nucleopolyhedrovirus (BmNPV) is a major viral pathogen found in silkworms, which leads to huge silk loss annually. In a recent lysine acetylome of silkworm infected with BmNPV, we focused on the heat shock cognate protein 70-4 (HSC70-4) lysine acetylation change due to the consequent nuclear accumulation and viral structure assembly. In this study, the genome replication, proliferation, and production of budded viruses (BVs) were arrested by HSP/HSC70 inhibitor treatment. However, HSC70-4 overexpression enhanced BmNPV reproduction. Furthermore, site-direct mutagenesis for acetylated mimic (K/Q) or deacetylated mimic (K/R) mutants of HSC70-4 demonstrated that lysine 77 (K77) deacetylation promotes HSC70-4 stability, viral DNA duplication, and HSC70-4 nuclear entry upon BmNPV challenge, and the nuclear propulsion of HSC70-4 after viral stimulus might be dependent on the interaction with the carboxyl terminus of HSC70-interacting protein (CHIP, an E3 ubiquitin ligase), followed by ubiquitin-proteasome system assistance. In this study, single lysine 77 deacetylation of HSC70-4 was deemed a part of the locomotive pathway for facilitating BmNPV proliferation and provided novel insights into the antiviral strategic development.